1873 Ga. Code 818 - (:unkn) unknown (My University, 1873)
§ 4528: Prohibited the carrying of any dirk, Bowie knife, pistol, or other deadly weapon to a court, election site, precinct, place of worship, or other public gathering site. Punishable by fine of $20-50 or imprisonment for 10-20 days.
Keywords: CARRY - CERTAIN PUBLIC PLACES